2008
DOI: 10.2215/cjn.03600807
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxemia is Related to Systemic Inflammation and Atherosclerosis in Peritoneal Dialysis Patients

Abstract: Conclusions: It was found that endotoxemia was probably common in PD patients, and the degree of circulating endotoxemia might be related to the severity of systemic inflammation and features of atherosclerosis. This result suggests that endotoxemia may have a contributory role to the systemic inflammatory state and accelerated atherosclerosis in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
155
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(170 citation statements)
references
References 37 publications
9
155
4
2
Order By: Relevance
“…This is in keeping with the only previous report (in PD patients) (21). There was a lack of association with hsCRP in the patient group as a whole, in contrast to the association in HD patients (with a generally higher degree of systemic inflammation).…”
Section: Discussionsupporting
confidence: 91%
“…This is in keeping with the only previous report (in PD patients) (21). There was a lack of association with hsCRP in the patient group as a whole, in contrast to the association in HD patients (with a generally higher degree of systemic inflammation).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, we noted higher levels of endotoxin in patients with eGFR.60 ml/min per 1.73 m 2 . Previous studies have reported elevated or unchanged endotoxin levels in patients with more advanced CKD (7,(26)(27)(28)(29). This apparent discrepancy may be explained by several factors.…”
Section: Discussionmentioning
confidence: 86%
“…The Bruneck Study showed that elevated plasma levels of endotoxin are associated with CVD in the general population (6). Endotoxemia has also been shown to be related to inflammation and atherosclerosis in peritoneal dialysis patients (7). However, the effect of subclinical endotoxemia in patients with CKD has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the epithelial barrier structure and function in turn amplifies local and systemic inflammation by allowing translocation of bacterial toxins and other noxious products into the intestinal wall and systemic circulation. Indeed, inflammation in the CKD population is frequently associated with endotoxemia without signs of clinical infection [13,14], and recent papers highlight bacterial translocation and its association with systemic inflammation in end-stage renal disease (ESRD) patients maintained on hemodialysis [15,16]. Serum pro-inflammatory cytokine levels (IL-1, TNF-a, IL-6, IL-13) and circulating endotoxin are significantly associated with increased mortality in hemodialysis patients [17][18][19], and systemic inflammation is strongly associated with comorbidities including cardiovascular disease, anemia, and malnutrition [20][21][22].…”
Section: Introductionmentioning
confidence: 99%